Distribution of Fim A Genotypes among Porphyromonas Gingivalis associated with Chronic Periodontitis in Al-Najaf Al-Ashraf City - Ahlam Kadhum Al-Yasseen (Journal of Global Pharma Technology, 2018)
This research aims to detect the prevalence of fim A genotypes I, Ib, II, III, IV and V among Porphyromonas  gingivalis related with periodontitis. Amplification of 16S rRNA gene showed that out of 150 DNA samples that extracted from subgingival plaque specimens of patients with chronic periodontitis only 40 DNA specimens were belonged to P. gingivalis and DNA sequencing demonstrated 98% homologous with P. gingivalis strain CP38 16S rRNA gene, partial sequence. fimA type IV gene was the most predominance with 27.5% followed by fimA type III with12.5%  while fimA type II show up with the lowest percentage (5%) while fimA type Ib was not identified. This finding denoted that  P. gingivalis that possess  fimA type IV was the most importance pathogens associated with  chronic periodontitisKeywords: P. gingivalis, Fim A genotypes, Periodontitis.